Incision and Curettage Versus Two Types of Intralesional Steroid Injections for the Treatment of Previously Operated Persistent Chalazion - Yasmena Abdulhadi; Bahjah Esehiyb; Khairia Sehib (AlQalam Journal of Medical and Applied Sciences, 2021)
Aims: To compare the effectiveness of two types of intralesional steroid injection [methylprednisolone acetate 40mg/ml (Depo-Medrol), and triamcinolone acetonide. 2mg (0.1ml)] versus surgical treatment (incision and curettage) in the treatment of recurrent chalazia. Methods. A prospective, interventional clinical study done in Benghazi in private eye clinic from January to October 2020. Sixty patients that met the inclusion criteria are randomized to receive either methylprednisolone acetate 40 mg/ml (Depo-Medrol), triamcinolone acetonide 2mg (0.1ml)] or incision and curettage by the same Ophthalmologist after giving informed consent. Were 20 cases for each procedure are divided, Patients were followed up at 0ne week, two weeks and at 6 weeks. A full examination was done, including: VA, IOP, size, location and duration of the chalazion before and after the treatment. All possible complications such as: skin changes, drug deposition in the skin, IOP changes, ecchymosis, fat hypertrophy is recorded. Results. In total 60 patients with recurrent chalazia were enrolled in this study included 20 patients for each group. Success rate was equal in all groups19(95%) of 20patients.Skin depigmentation were noted in 2 cases, skin deposition &ecchymosis occurred in 6 cases with intralesional steroid injection. Conclusion. Both intralesional injections (TA&Depo) &surgical treatment are very effectives procedures in treatment of recurrent chalazia with equal high success rates in all procedures.